Non-carbapenem Drugs for Patients with Bacteremia caused by Extended-Spectrum β-Lactamase-Producing Enterobacteriaceae: Piperacillin-Tazobactam - Oh, Hyunjoo; Lee, Seunghee; Kim, Misun; Heo, Sang Taek; Yoo, Jeong Rae (The Korean journal of medicine, 2024)
Background/Aims: Carbapenems are recommended for treating bacteremia caused by extended-spectrum β-lactamase (ESBL) producing Enterobacteriaceae (ESBL-E). However, this has resulted in a significant rise in the utilization of carbapenems in cases of ESBL-E infection. We evaluated the clinical outcomes of patients with ESBL-E bacteremia treated with non-carbapenem antimicrobials.Methods: We conducted a retrospective case-control study of a cohort of patients with documented ESBL-E bacteremia from January 2021 to December 2021. The patients were divided into two groups according to whether they received non-carbapenem or carbapenem therapy. The rates of treatment failure, 30-day mortality and microbiologic failure, and the durations of hospitalization and of antimicrobial therapy were compared between the two groups. Antimicrobial susceptibility testing and phenotypic identification of ESBL-E were performed using the Vitek 2 system.Results: Of 118 patients with ESBL-E bacteremia, 54 received non-carbapenem drugs (non-carbapenem group [NCG]) and 64 received carbapenems (carbapenem group [CG]). Treatment failure at 30 days occurred in 16.7% of the patients in the NCG and in 18.8% in the CG (p = 0.65). The 30-day mortality rate was 14.8% in the NCG and 17.2% in the CG (p = 0.63). Extra-urinary tract infection and prior antimicrobial therapy within 30 days were risk factors for treatment failure in patients with ESBL-E bacteremia. The clinical outcomes did not differ significantly between the two groups, challenging the prevailing preference for carbapenems in the treatment of ESBL-E bacteremia.Conclusions: Non-carbapenem antimicrobials such as piperacillin/tazobactam are recommended for patients with mild ESBL-E bacteremia in South Korea.